Association Between Menopausal Estrogen-Only Therapy and Ovarian Carcinoma Risk. Issue 8 (August 2016) - Lee, Alice W.; Ness, Roberta B.; Roman, Lynda D.; Terry, Kathryn L.; Schildkraut, Joellen M.; Chang-Claude, Jenny; Doherty, Jennifer A.; Menon, Usha; Cramer, Daniel W.; Gayther, Simon A.; Risch, Harvey; Gentry-Maharaj, Aleksandra; et al.
Abstract : (Abstracted from Obstet Gynecol 2016;127:828–836) Menopausal hormone therapy (HT), containing estrogens, is most commonly used by postmenopausal women to relieve climacteric symptoms and prevent osteoporosis. The therapy has, however, been strongly linked with an increased risk of ovarian carcinoma; although it is yet to be established whether differences exist by disease histotype or by the duration and timing of use of HT.